Economic uncertainty and subjective inflation expectations - Tobias Rossmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Measuring economic uncertainty is crucial for understanding investment decisions by individuals and firms. Macroeconomists increasingly rely on survey data on subjective expectations. An innovative approach to measure aggregate uncertainty exploits the rounding patterns in individuals' responses to survey questions on inflation expectations (Binder, 2017). This paper uses the panel dimension of household surveys to study individual-level heterogeneity in this measure of individual uncertainty. The results provide evidence for the existence of considerable heterogeneity in individuals' response behavior and inflation expectations.
Keywords: C10; D80; D83; D84; E31; 330; Uncertainty; inflation; expectations; mixture models